Karakteristik Buah Dan Biji Terong (Solanum Melongena .L var. Kenari) Setelah Diberi Ekstrak Air Akar Eceng Gondok (Eichhornia crassipes) - Fida Alvitasari; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2019)
Thai aubergine or eggplant, or goes by local name terong kenari (Solanum melongena L. var Kenari), is a vegetable included in the family Solanaceae. Eggplant loved by most of Indonesians, either eaten fresh or cooked. However, some often despise eggplant’s seeds as it may cause digestive problem. Plant hormone in controlling plants’ growth, such as giberelin, are frequently used to produce seedless or no-seed eggplant. This study is conducted to test the impact of water hyacinth, or goes by local name eceng gondok (Eichhornia crassipes), root extract treatment in the characteristic of eggplant (Solanum melongena L. var Kenari) fruit and seeds. This research is done in experimental manner, using the completely randomized design, including four different extract’s concentration; 0 g/L, 50 g/L, 100 g/L, and 150 g/L; and one giberelin treatment that are given five times, repeatedly. According to the research conducted, the water hyacinth root extract treatment results in the increase of the quantity and weight of the eggplant, and also the reduction in seeds, as it also affects the fruit skin layer thickness. As in the study, the optimum outcome is obtained with the concentration of 150 g/L water hyacinth root extract; which result in average number of fruit 6.6 for each plant, average weight 179.57 gram per fruit, average number of seeds 561 per fruit, average weight 6.14 gram per seed, and average skin thickness 0.78 in each eggplant. Keywords: Eggplant, gibberellin hormone, water hyacinth, characteristic of eggplant fruit and seeds